2018
DOI: 10.2174/1745017901814010296
|View full text |Cite
|
Sign up to set email alerts
|

Grandparents - Grandchildren Relationship in Iran, 2017

Abstract: Introduction: With the continuing growth of aged populations, it is imperative to find ways to maintain and improve the quality of life in old age. It has been documented that grandparents-grandchildren relationship is significantly contributed to quality of life of older adults. This study was conducted to identify the status and associated factors of grandparents-grandchildren relationship in a sample of Iran. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Following physical activity and health instructions has been identified as positively associated with the improved quality of life in the elderly (18)(19)(20)(21). Also, it has been shown that grandparents-grandchildren relationship is significantly contributed to quality of life of older adults (22).…”
Section: Introductionmentioning
confidence: 99%
“…Following physical activity and health instructions has been identified as positively associated with the improved quality of life in the elderly (18)(19)(20)(21). Also, it has been shown that grandparents-grandchildren relationship is significantly contributed to quality of life of older adults (22).…”
Section: Introductionmentioning
confidence: 99%